Flirting with the past - Newell, Kaylie (Harlequin special edition, 2024)
"Only love can make them whole. Poppy Sawyer has spent years struggling with survivor's guilt over the car wreck that killed her high school boyfriend. But when her grandfather wills her part of his antiques shop in Christmas Bay, she returns home to face the pain in her past-and Justin Frost, the deceased's brother. Neither expected their long-buried, forbidden attraction would spark at their first meeting. Nor the healing they find in each other's arms. But guilt is a hard obstacle to overcome, as is Justin's family. The only way forward together is to find forgiveness--with their loved ones and each other." -- Page [4] cover.